Blocking CXCR4+ CD4+ T cells reprograms Treg-mediated immunosuppression via modulating the Rho-GTPase/NF-κB signaling axis - Canhui Cao; Miaochun Xu; Ting Peng; Xiaojie Liu; Shitong Lin; Yashi Xu; Tian Chu; Shiyi Liu; Ping Wu; Bai Hu; Wencheng Ding; Li Li; et al. (Genome Medicine)
Abstract Background While clinical trials have shown that CXCR4 antagonists can enhance the efficacy of cancer immunotherapy, the molecular mechanisms by which CXCR4 modulates the tumor microenvironment remain poorly understood. We recently identified CXCR4 as a regulator of exhausted CD8+ T cell phenotypes in cancer. Here, we investigate its role in orchestrating regulatory T (Treg) cell-mediated immunosuppression within tumors. Methods We conducted meta-analyses of single-cell RNA-seq datasets from pan-cancer tissues to characterize CXCR4 expression patterns in CD4+ T cells. Using CXCR4 antagonists and conditional knockout mice (Cxcr4 flox/flox , Lck Cre ), we inhibited Treg phenotypes in vivo. Through single-cell transcriptomics and single-cell ATAC-seq of the cervical cancer mouse model, phosphoproteomics, and ChIP-seq analyses, we elucidated how CXCR4 blockade in CD4+ T cells suppresses activated Treg phenotypes by modulating the Rho-GTPase/NF-κB signaling axis. We further integrated RNA-seq data, clinical trial datasets (NCT02826486 and NCT04516616), and human organoid models to validate the therapeutic potential of CXCR4 inhibition in enhancing antitumor immunotherapy. Results Single-cell transcriptomics of CD4+ T cells across multiple cancers revealed CXCR4 expression was associated with Treg cell developmental trajectories. Pharmacological and genetic inhibition of CXCR4 inhibited Treg phenotypes in cervical cancer and breast cancer. Mechanistically, phosphoproteomics and ChIP-seq analyses unveiled that blocking CXCR4+ CD4+ T cells reduced activated Treg phenotypes by modulating the Rho-GTPase/NF-κB signaling axis. Single-cell transcriptomic and multi-omic analyses demonstrated that blocking CXCR4+ CD4+ T cells promoted immunotherapy via reprogramming Treg-mediated immunosuppression. Furthermore, clinical trial data and human cervical cancer organoids confirmed that blocking CXCR4 enhances antitumor immunotherapy by reducing Treg phenotypes. Conclusions Our study highlights the crucial role of CXCR4 in deriving Treg-mediated immunosuppression via regulating the Rho-GTPase/NF-κB signaling axis, informing the potential of combining CXCR4 blockades with T cell-targeted immunotherapies.